Pengaruh Latihan Bola Plastik dan Bola Karet terhadap Keterampilan Passing Atas Bola Voli Siswa Ekstrakurikuler MTs Bumi Agung (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
The problem of this research is that passing is still not right on target, has not mastered the upper passing technique correctly, lack of mastery and control of the ball, so the problem in volleyball extracurricular is the lack of volleyball upper passing ability. The research method used in this study is the experimental research method. The design in this study uses Two Group Pretest Posttest. This Two Group Pretest Posttest only has measurement result data, namely pretest and posttest measurements. the results of the t value in the experimental group using a plastic ball are -19.312> 1.7613 and in the experimental group using a rubber ball are -18.862> 1.7613. From the results of the T test table, the comparison of the results of training using plastic balls and rubber balls is to see the average value (Mean) on the pretest results using a plastic ball, the average value is 15.33, the posttest using a plastic ball obtained an average value of 27.13 with a difference in increase of 11.8. While the average value (Mean) on the pretest results of the exercise using a rubber ball, the average value was 15.27, the posttest using a rubber ball obtained an average value of 27.73 with a difference of 12.46. Thus, it can be concluded that training using a rubber ball is more effective in improving upper passing skills compared to training using a plastic ball.